A Design of CP-MIMO System with Elements of a Diamond-Ring Slot for 5G Mobile-Phone - Alyaa Sami Abdullah; Seham A. Hashem; Mahmood F . Mosleh (Journal of Techniques)
This paper proposed a Circular Polarization (CP) smartphone antenna Multiple Input Multiple Output (MIMO) system with elements of a diamond ring slot for next-generation (5G). The model's composition contains four elements. Each element has a dual-fed diamond ring slot arranged at the four smartphone corners Printed Circuit Board (PCB). A cheap FR-4 substrate with using a size of 75 x 150 mm2 as the design dielectric mater. 50-Ohm microstrip-lines T-shaped feeds the antenna ports. The orthogonal positioning of microstrip feed lines is used to achieve polarization and diversity characteristics. The paradigm results show that each port operated with an operating frequency of 3.74 GHz, with the overall system running at 3.84 GHz. Also, the results show that the MIMO system is suitable for operation in a sub-6 band that qualified for 5G smartphone applications.